2022
DOI: 10.1186/s12981-022-00450-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence trends and risk factors associated with HIV, syphilis, and hepatitis C virus among pregnant women in Southwest China, 2009–2018

Abstract: Objective This study investigated prevalence trends and identified the associated factors of HIV, syphilis and hepatitis C virus (HCV) among pregnant women in the Guangxi Zhuang Autonomous Region (Guangxi), Southwest China. Methods Serial cross-sectional surveys were performed annually among pregnant women in Guangxi from 2009 to 2018. Blood specimens were collected to test the prevalence of HIV, syphilis and HCV. Cochran–Armitage analysis was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In areas with high HIV prevalence, maternal HIV screening helps to identify HIV-infected PW at an early stage and provides timely drug interventions to interrupt mother-to-child transmission,34 which has a positive effect on reducing vertical transmission 35 36. Urine reagent strips showed satisfactory ROC curves in maternal HIV-1 antibody screening, but there were two false-positive tests out of 1000 tests.…”
Section: Discussionmentioning
confidence: 99%
“…In areas with high HIV prevalence, maternal HIV screening helps to identify HIV-infected PW at an early stage and provides timely drug interventions to interrupt mother-to-child transmission,34 which has a positive effect on reducing vertical transmission 35 36. Urine reagent strips showed satisfactory ROC curves in maternal HIV-1 antibody screening, but there were two false-positive tests out of 1000 tests.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that 500,000 pregnant women from Shenzhen (China) underwent syphilis screening and that the mother-to-child transmission rate of syphilis decreased significantly from 54/100,000 to 22/100,000 (27). Another study in China analyzed 23,879 pregnant women from 2009 to 2018 and found that the prevalence of syphilis among pregnant women decreased from 1.5 to 0.3% after the implementation of prenatal screening (28). The above two studies indicate that regular prenatal syphilis screening can greatly reduce the incidence of congenital syphilis.…”
Section: Preventionmentioning
confidence: 98%
“…Moreover, the majority of women in Tibet rarely visit hospitals voluntarily, except in emergencies, and they are uninclined to pay for, even affordable, screening programs. Therefore, government-financed HPV primary screening programs for all the population at right ages ( 16 ) may be the best choice for women in Tibet.…”
Section: Introductionmentioning
confidence: 99%